Faktor-Faktor yang Mempengaruhi Stres Akademik - Nur Mawakhira Yusuf; Jannatul Ma’wa Yusuf (Psyche 165 Journal, 2020)
Academic stress is an individual condition that arises because of the amount of pressure or academic demands that exceed their capacity so that individuals feel burdened. The purpose of this study is to identify the factors that influence academic stress. Literature searches were carried out in the electronic database Researchgate, Scopus, Springer, and Google Schoolar using the keywords "academic stress and academic stress". The research strategy of this research includes the type of systematic research reviewing the literature using qualitative methods (meta-synthesis). Suggestions used in this research are meta-ethnograph. The search results show that showing that academic stress is influenced by internal and external factors. Internal factors consist of self-efficacy, hardiness, optimism, achievement motivation and procrastination, while external factors consist of social support.